Automated Data Security Model Using Cryptography Techniques in Cloud Environment - M. Jagadeeshwar, D. Shanthi, Mada Prasad (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing, a highly debated research frontier, offers the dual advantage of cost reduction and enhanced scalability and flexibility in computing services. Its widespread adoption spans diverse sectors such as the military, healthcare, industry, and education, facilitating the storage of vast datasets. Users can access shared resources, including software and information, at their convenience from any location. However, the security of cloud-stored data, categorized as private, public, or sensitive, poses challenges, especially when entrusting third-party providers with confidential information. Acknowledging that security is a joint responsibility of both enterprises and customers, even industry giants stress the need for a collaborative approach. Encrypting information stored in the cloud becomes imperative from the client's standpoint to prevent unauthorized access. Numerous challenges arise in cloud data storage, necessitating innovative solutions, and various algorithms have been developed to address these issues. This study employs cryptographic techniques to address security concerns, with a focus on the Asymmetric Key Cryptography with Related Key Set (AKC-RKS) technique. The paper introduces novel safety mechanisms using the AKC-RKS technique, comparing the proposed model with traditional encryption methods. The results demonstrate a high level of data security in the proposed model, showcasing the efficacy of cryptographic techniques in fortifying data security within cloud environments.